2017
DOI: 10.1016/j.chemosphere.2017.05.167
|View full text |Cite
|
Sign up to set email alerts
|

Brominated and phosphate flame retardants (FRs) in indoor dust from different microenvironments: Implications for human exposure via dust ingestion and dermal contact

Abstract: Indoor dust has been widely used to monitor flame retardants (FRs) in indoor environment, but most studies only focused on floor dust. In the present study, FRs were examined in indoor dust from different locations. Dust from air conditioner (AC) filters, beddings, floor, and windows in bedrooms, and dust from AC filters, printer table surface, computer table surface, floor, and windows in offices were collected, respectively. Polybrominated diphenyl ether congener 209 (BDE 209) and decabromodiphenyl ethane (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The median EDI for toddlers (48.0 ng/kg-bw/day) from indoor environment was the highest, followed by infants (42.0 ng/kg-bw/day), children (36.2 ng/kg-bw/ day), teenagers (20.7 ng/kg-bw/day) and adults (11.8.0 ng/kg-bw/ day), suggesting the much more sensitivity to OPE exposure for young people than adults. The estimated EDIs in this study were comparable with the EDIs calculated in Beijing (Wu et al, 2016;Cao et al, 2019a;Wang et al, 2019) and Guangdong (He et al, 2015;Zheng et al, 2015;Zheng et al, 2017), China. Additionally, TCIPP was the most abundant OPE for all age group exposure with the EDIs ranging from 4.16 ng/kgbw/day to13.1 ng/kg-bw/day.…”
Section: Estimated Daily Intakessupporting
confidence: 82%
“…The median EDI for toddlers (48.0 ng/kg-bw/day) from indoor environment was the highest, followed by infants (42.0 ng/kg-bw/day), children (36.2 ng/kg-bw/ day), teenagers (20.7 ng/kg-bw/day) and adults (11.8.0 ng/kg-bw/ day), suggesting the much more sensitivity to OPE exposure for young people than adults. The estimated EDIs in this study were comparable with the EDIs calculated in Beijing (Wu et al, 2016;Cao et al, 2019a;Wang et al, 2019) and Guangdong (He et al, 2015;Zheng et al, 2015;Zheng et al, 2017), China. Additionally, TCIPP was the most abundant OPE for all age group exposure with the EDIs ranging from 4.16 ng/kgbw/day to13.1 ng/kg-bw/day.…”
Section: Estimated Daily Intakessupporting
confidence: 82%
“…Numerous other worker groups are expected to be more heavily exposed than the general population, especially when workers are in direct contact with large volumes of PEFRs as pure chemicals or at high concentrations in technical formulations at industrial sites and in manufacturing (e.g., at electronics dismantling facilities or electronic goods recycling areas). Measurements of PEFRs in air and dust in various occupational settings have also shown that the work environment may noticeably contribute to external exposure to PEFRs (Makinen et al, 2009;Ali et al, 2014;Wei et al, 2015;Zheng et al, 2017;Zhou et al, 2017;Muenhor et al, 2017;Bello et al, 2018;Ceballos et al, 2018;. Nevertheless, information on the nature and extent of occupational exposures to PEFRs, especially in terms of measurements of an individual's internal exposure, is still limited and warrants further investigations (characterization, quantification, and contribution to total PEFR burden).…”
Section: Workersmentioning
confidence: 99%
“…The median concentration of total PEFRs was around 10-100 ng/g of lipids in breast milk from Sweden and several Asian countries, indicating that substantial exposure occurs at a young age via breastfeeding (Sunddkvist et al, 2010;Kim et al, 2014). The parent compounds (Liu et al, 2016;Zhao et al, 2016;Li et al, 2017;Ma et al, 2017;Qiao et al 2017) and their metabolites (Bui et al, 2017) were found in human serum and blood in a few studies. The metabolism of parent PEFRs tends to occur rapidly and the measurement of metabolites concentrations in urine is generally preferred to the invasive measurement of the nonmetabolized chemicals in serum for exposure assessment.…”
Section: Occurrence Of Pefrs In Other Human Samplesmentioning
confidence: 99%
“…The maximum concentration was 1800 μg/g for TCEP and 350 μg/g for TCPP in daycare centres and 860 μg/g for TDCPP in homes. OPFRs in dust were also measured in building material markets, private cars, floor/carpet stores, offices, bedrooms and schools 15,16 with the total concentration ranging from 5.9 to 4800 μg/g.…”
Section: Organophosphorus Flame Retardantsmentioning
confidence: 99%